Prognostic Role of Prostate-specific Antigen Isoforms and Their Early Kinetics in Patients With Metastatic Castration-resistant Prostate Cancer Receiving New Generation Androgen Receptor Targeted Agents - Fiala, Ondřej; Hošek, Petr; Korunková, Hana; Tkadlecová, Michaela; Hora, Milan; Šiková, Dominika; Stránský, Petr; Fínek, Jindřich; Kučera, Radek; Windrichová, Jindra; Topolčan, Ondřej (In vivo (Athens, Greece), 2025)
BACKGROUND/AIM: New generation androgen receptor-targeting agents (ARTA) have been in the spotlight for their efficacy in metastatic castration-resistant prostate cancer (mCRPC). Prostate-specific antigen (PSA) represents one of the most commonly used serum cancer biomarkers worldwide. The present retrospective study focused on the prognostic role of serum PSA isoforms and their early dynamics in mCRPC patients treated with abiraterone acetate (ABI) or enzalutamide (ENZ). PATIENTS AND METHODS: The association between outcomes of 334 mCRPC patients treated with ABI or ENZ and the levels of serum total PSA (tPSA), free PSA (fPSA), [-2]proPSA and the Prostate Health Index (PHI) at baseline and one month after treatment initiation was analyzed retrospectively. RESULTS: In the multivariable Cox proportional hazards models, baseline tPSA>50 μg/l (p<0.001), and [-2]proPSA>300 ng/l (p=0.017) remained independent significant factors associated with inferior OS, while baseline fPSA>1.75 μg/l (p=0.050) and Δ [-2]proPSA >-50% approached statistical significance (p=0.062). The results of ROC analyses assessing the ability of baseline tPSA, fPSA, and [-2]proPSA to predict mortality within two years showed area under the curve (AUC) values of 0.709, 0.685, and 0.740, respectively. Among the subgroup with baseline tPSA≤20.0 μg/l, the results of ROC analyses for baseline tPSA, fPSA and [-2]proPSA showed AUC values of 0.441, 0.682, and 0.688, respectively. CONCLUSION: Our results suggest a significant correlation between pretreatment serum levels of tPSA and [-2]proPSA with OS in mCRPC patients receiving ARTA.
Keywords: Protein Isoforms; senioři; metastázy nádorů; (−2)proPSA; Castration-resistant prostate cancer; senioři nad 80 let; androgenní receptory; Benzamides; enzalutamide; Retrospective Studies; Abiraterone Acetate; Prognosis; Prostatic Neoplasms, Castration-Resistant; výsledek terapie; Middle Aged; ROC Curve; mužské pohlaví; nádory prostaty rezistentní na kastraci; Phenylthiohydantoin; prostatický specifický antigen; benzamidy; ROC křivka; fenylthiohydantoin; Prostate-Specific Antigen; Biomarkers, Tumor; Aged, 80 and over; Neoplasm Metastasis; prognóza; nádorové biomarkery; Receptors, Androgen; abirateron; protein - isoformy; retrospektivní studie; Humans; PSA; lidé středního věku; free PSA; ARTA; Aged; nitrily; Treatment Outcome; abiraterone acetate; lidé; Male; Nitriles